2002
DOI: 10.1557/proc-755-dd6.12
|View full text |Cite
|
Sign up to set email alerts
|

Ag Ion-Exchange Reactions of Cu2P3I2 and Cu2P1.8As1.2I2

Abstract: A variety of ion exchange techniques for Cu 2 P 3 I 2 and its mixed pnictogen analog Cu 2 P 1.8 As 1.2 I 2 have been studied. Ag 2 P 3 I 2 is an existing material, previously prepared from Cu 2 P 3 I 2 by ion exchange of Ag + for Cu + in aqueous medium. This method is compared to nonaqueous (ionic liquid) and solid state routes for ion exchange. Additionally, the new compound Ag 2 P 1.8 As 1.2 I 2 with cell parameters a = 15.838(17) Å, b = 13.684(10) Å, c = 15.580(17) Å and β = 117.63(7)°, has been prepared by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The residual pellet has a similar pattern to that for the crystals, along with peaks corresponding to CuI. Energy dispersive spectroscopy (EDS) on single crystals imaged in the scanning electron microscope (SEM) indicated the presence of Cu, P, As, and I, [15] thus implying that the compound is a quaternary phase. Quantification of As incorporation in crystals of 20 %, 35 %, 40 %, 45 %, and 55 % As samples was achieved by inductively coupled plasma-mass spectrometry (ICP-MS) and the data are presented in Table 1.…”
Section: Resultsmentioning
confidence: 83%
“…The residual pellet has a similar pattern to that for the crystals, along with peaks corresponding to CuI. Energy dispersive spectroscopy (EDS) on single crystals imaged in the scanning electron microscope (SEM) indicated the presence of Cu, P, As, and I, [15] thus implying that the compound is a quaternary phase. Quantification of As incorporation in crystals of 20 %, 35 %, 40 %, 45 %, and 55 % As samples was achieved by inductively coupled plasma-mass spectrometry (ICP-MS) and the data are presented in Table 1.…”
Section: Resultsmentioning
confidence: 83%
“…However, Möller and Jeitschko reported that addition of KCN permitted facile exchange of Cu + by Ag + in Cu 2 P 3 I 2 without silver deposition, and proposed that the reaction proceeds according to eq 1 . Our attempts to employ excess KCN with Cu 2 P 1.8 As 1.2 I 2 did produce a material with Ag incorporation, according to energy dispersive spectroscopy (EDS), but it was X-ray amorphous …”
mentioning
confidence: 90%
“…The approach described herein is based on the results from Ag + ion-exchange reactions performed on Cu 2 P 1.8 As 1.2 I 2 to prepare the corresponding Ag analogue . Reactions in aqueous solutions with AgNO 3 invariably produced elemental silver as a byproduct, along with Ag 2 P 1.8 As 1.2 I 2 .…”
mentioning
confidence: 99%